Teacher Personality Competencies According to Ibnu Sahnun in the Book of Adab Al-Mu'allimin and According to Az-Zarnuji in the Book of Ta'lim Al-Muta'allim - Wicaksono, Imam Alhakam; Mustofa, Triono Ali; Muthoifin, Muthoifin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
A good teacher is a teacher who has a complete personality, is virtuous, mature, has faith, morals, is disciplined and is responsible. The teacher's personality influences the formation of a student's personality because it is seen as the starting point for someone to become a successful educator. Thus, efforts must continue to be made to increase teacher personality competence. The aim of this research is to determine teacher personality competencies, similarities and differences, and to find the relevance of teacher personality competencies according to Ibnu Sahnun in the book Adab Al-Mu'allimin and according to Az-Zarnuji in the book Ta'lim Al-Muta'allim. This type of research is library research using a philosophical approach. The primary sources for this research were taken from the book Adab Al-Mu'allimin by Ibnu Sahnun and the book Ta'lim Al-Muta'allim by Az-Zarnuji. The validity tests of the data used in this research are testing the degree of trust, testing transferability, testing reliability, testing certainty. Data analysis techniques include data reduction, data presentation, drawing conclusions and verification. The results of this research are; 1) Teacher personality competencies in the book Adab Al-Mu'allimin by Ibnu Sahnun are acting fairly, avoiding discrimination towards students, compassion, not acting when emotional, sincere, responsible, moral and devout. Meanwhile, according to Az Zarnuji, teacher personality competencies in his book Ta'lim Al-Muta'allim are sincere, authoritative, affectionate, wara', and tawadlu'. 2) The similarity in teacher personality competence between the two books lies in sincerity and compassion. Meanwhile, the difference in personality competence between the two books lies in moral development and being fair. 3) The relevance of the teacher's personality competency in the book Adab Al-Mu'allimin by Ibnu Sahnun and Az Zarnuji in their book Ta'lim Al-Muta'allim with the teacher's personality competency according to the Law on Teachers and Lecturers, namely stable, stable and mature, authoritative, and noble character.